Particulate polyaryletherketones with amine end functionalisation by a Friedel Crafts dispersion polymerisation - Smith, K; Towle, I; Pratte, J; Maskell, R; Moloney, M (Elsevier, 2016)
Amine end-capped polyaryletherketones (PAEKs) are available by a dispersion process using a protection-deprotection strategy with an end-capping aminoaromatic derivative which adds no further steps to the dispersion polymerisation method. A model compound approach was employed to demonstrate successful amine attachment to the polymer, together with its compatibility and suitability within the polymer system. This approach was also successful for linear and trifunctional versions. Scale-up of the PAEK dispersion synthesis to 300 g batches was achieved. Amine end-capped poly(ether ketone ketone) (PEKK) with 100:0, 80:20, 60:40 terephthaloyl (T):isophthaloyl (I) ratios, along with branched PEKK and PEKK-imide copolymers, were synthesised. Mechanical analysis confirmed a substantial increase in fracture toughness on incorporation of the functionalised PEKK particles in an epoxy resin laminate when compared to non-functionalised PEKK particles.